2016
DOI: 10.1002/cjce.22519
|View full text |Cite
|
Sign up to set email alerts
|

Effects of particle size on the catalytic performance of MWCNTs supported alkalized MoS2 catalysts promoted by Ni and Co in higher alcohols synthesis

Abstract: A series of nano‐sized alkalized MoS2 catalysts promoted by Ni and Co supported on multi‐walled carbon nanotubes (MWCNTs) were prepared via the reverse microemulsion technique with water to surfactant (W/S) molar ratios (molwater · mol−1surfactant) of 1–12. All prepared catalysts were extensively characterized by ICP, BET, CO chemisorption, XRD, TPR, and TEM techniques. They were assessed in a fixed‐bed micro‐reactor to find their performance in higher alcohol synthesis from syngas. The results were compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…The reduction temperature of Mo–S species in the Mo–S/Al 2 O 3 catalyst increased slightly from 203 to 214 °C after 72 h of WGS reaction. The increased reduction temperature of Mo–S species could be attributed to the increased ordering of the Mo–S species and the onset of crystallization of a Mo–S phase, in good agreement with TEM observations and XRD patterns of the used Mo–S/Al 2 O 3 catalyst shown in Figures and , respectively. The Mo–S species associated with large MoS 2 slabs were previously reported to show low catalytic activity .…”
Section: Results and Discussionsupporting
confidence: 87%
“…The reduction temperature of Mo–S species in the Mo–S/Al 2 O 3 catalyst increased slightly from 203 to 214 °C after 72 h of WGS reaction. The increased reduction temperature of Mo–S species could be attributed to the increased ordering of the Mo–S species and the onset of crystallization of a Mo–S phase, in good agreement with TEM observations and XRD patterns of the used Mo–S/Al 2 O 3 catalyst shown in Figures and , respectively. The Mo–S species associated with large MoS 2 slabs were previously reported to show low catalytic activity .…”
Section: Results and Discussionsupporting
confidence: 87%
“…[22] One study has shown that Co catalyst samples with smaller nanoparticles ($5 nm) led to greater CO conversion (66.8 %) with much higher alcohol selectivity (37.8 %) than the samples with larger particles ($17 nm). [32]…”
Section: Tem Analysismentioning
confidence: 99%
“…The composition of the two phases strongly depends on the preparation methods [9] . The common methods for the preparation of alkali modified Co-MoS 2 catalysts include impregnation/coprecipitation methods, reverse microemulsion technique and mechano-chemical activation and so on [6,10,11] . Taking the impregnation as an example, the as-prepared Co-MoS 2 catalyst mainly contained the Co-Mo-S phase if the Co/Mo atomic ratio less than 0.4.…”
Section: Introductionmentioning
confidence: 99%